Characterization of severe maxillofacial trauma in two emergency departments in Havana, Cuba - Denia Morales Navarro; Vanessa Barreto Orozco; Laura Durañona Álvarez; Agustín Rodríguez Soto (Editorial Ciencias Médicas, 2020)
Introduction: Facial injuries may affect patients' capacity to eat, speak and interact. Objective: Characterize severe maxillofacial trauma in the emergency departments of General Calixto García University Hospital and Miguel Enríquez Hospital in Havana, Cuba. Methods: A descriptive cross-sectional multicenter study was conducted in the emergency departments of General Calixto García University Hospital and Miguel Enríquez Hospital from March 2017 to March 2019. The study universe was patients diagnosed with severe maxillofacial trauma. The qualitative variables were sex, etiology, consumption of alcoholic beverages and injuries, whereas the quantitative variable was age. A data collection form was developed and the information was stored in a database. Data were expressed in whole numbers, percentages and statistical tables. A search was performed for the relationship between the variables. Results: Male sex constituted 80.6% of the sample. The best represented age group was 18-30 years (33.3%), followed by 31-40 (25.0%). In 41.7% of the patients the trauma was related to traffic accidents, and in 30.6% to interpersonal violence. Alcohol breath was detected in 51.9% of the patients, among them most of those cared for at Miguel Enríquez Hospital. There was a predominance of wounds larger than 2 cm, followed by wounds under that length (61.1% and 32.4%, respectively) and mandibular fracture (51.9%). Conclusions: A predominance was found of the male sex and the 18-30 years age group; the main etiology was traffic accidents, followed by interpersonal violence; the most common soft tissue injuries were wounds larger than 2 cm, whereas the most common hard tissue injuries were mandibular fractures. A significant association was found with consumption of alcoholic beverages among the patients treated at Miguel Enríquez Hospital.